Analisis Kesulitan Belajar Siswa Dalam Pembelajaran Daring Pada Mata Pelajaran IPS Kelas V SDN Cigadung 5 - Pandela, Dita; Ridwan, Ita Rustiati; Susilawati, Susilawati (Didaktika, 2021)
Ideally, learning activities are carried out face-to-face, where the process of learning activities is carried out directly with a meeting between teachers and students in one place without going through any intermediaries. since the issuance of government policies that require the community to carry out all activities from home, face-to-face learning can no longer be done. The purpose of online learning is to make alternatives so that the learning process can continue as usual. This study aims to determine students' learning difficulties when studying online in social studies subjects in class V SDN Cigadung 5. The approach used in this study is qualitative. The method used in this research is the case study method. Data collection techniques in this study were through document analysis, interviews with school principals, class teachers, and parents of students, as well as questionnaires, addressed to 26 fifth grade students related to online learning difficulties in social studies subjects. The implementation of online learning, of course, creates obstacles during the learning process. Because online learning is a new thing, both students and teachers have previously been used to carrying out face-to-face learning. This can be seen from the results of the questionnaire recapitulation which has been filled out by 26 students. Students who answered correctly on the online learning difficulty questionnaire on social studies subjects were 794.7% while students who answered incorrectly were 1,220.7. This shows that more students answered incorrect statements in the questionnaire. So it can be concluded that SDN Cigadung 5, especially in class V, has difficulties when learning online in social studies subjects.